Dynamical studies of the ferroelectric domain structure in triglycine sulfate by voltage-modulated scanning force microscopy - V. Likodimos; Orlik, X.K.; Pardi, L.; Labardi, M.; Allegrini, M. (Journal of Applied Physics, 2000)
Voltage-modulated scanning force microscopy has been employed to investigate the dynamics of ferroelectric domains as a function of time and temperature in triglycine sulfate (TGS) single crystals. Branching of the domain structure and nucleation of fine domain patterns by internal fields of thermal origin have been directly observed on the submicron scale. Domain coarsening after quenching TGS samples from the paraelectric phase into the ferroelectric one has been studied, revealing a nonlinear time dependence of the characteristic correlation domain length and supporting the validity of dynamical scaling law and the conservation of the total surface charge. Substantial differences in the evolution of the domain structure have been detected during cooling or heating treatment in the ferroelectric phase. Domain contrast is shown to monitor the ferroelectric phase transition through its temperature dependence, reflecting the competition between electrostatic and piezoelectric effects. © 2000 American Institute of Physics.